IFNγ as an Immune Response in Groupers Infected by Viral Nervous Necrosis. Issue 1 (October 2021) - Sakinah Junirahma, Nur; Yanuhar, Uun; Musa, Muhammad
Abstract: One of the diseases reported to have infected groupers is Viral Nervous Necrosis (VNN) which can cause mass mortality in the larval stage of up to 100%. The nervous system of the fish so that the fish will lose their nerve control, develop weakness in motion, and cause death. In fish teleost, interferon (IFN) plays an important role in non-specific responses, especially in maintaining viral infections in vertebrates. The purpose of this study was to determine the immune response of the brain, kidney, and eye tissue receptors of grouper infected with Viral Necrosis (VNN) through flowcytometric analysis. The method used in this research is descriptive by analyzing and analyzing the IFNγ response in the brain, kidney, and eye tissue of VNN-infected groupers and healthy fish through flowcytometric analysis. The results of flowcytometric analysis showed that there was an immune response formed in the brain, kidney, and mouse grouper tissue by forming qualitative immune cells, namely the IFNγ immune response as a pro-inflammatory response to cells. The analysis showed that the IFNγ response in healthy grouper fish brain tissue was 0.21%, and VNN-infected fish was 0.55%. Healthy grouper fish eyes were 14.05%, and VNN infected fish was 17.73%. Then the kidney tissue of healthy grouper was 8.54%, and grouper infected with VNN was 16.08%. The response of all organs showed that fish had higher IFNγ values. IFNγ is important in the system due in part to its ability to inhibit direct viral replication, and most importantly its immunomodulatory effect.